Providing for the casualties of war the American experience through World War II - Rostker, Bernard (Santa Monica, CA RAND, 2013)
War has always been a dangerous business, bringing injury, wounds, and death, and -- until recently -- often disease. What has changed over time, most dramatically in the last 150 or so years, is the care these casualties receive and who provides it. Medical services have become highly organized and are state sponsored. Diseases are now prevented through vaccination and good sanitation. Sedation now ameliorates pain, and antibiotics combat infection. Wounds that once meant amputation or death no longer do so. Transfers from the field to more-capable hospitals are now as swift as aircraft can make them. The mental consequences of war are now seen as genuine illnesses and treated accordingly, rather than punished to the extreme. Likewise, treatment of those disabled by war and of veterans generally has changed markedly -- along with who supplies these and other benefits. This book looks at the history of how humanity has cared for its war casualties, from ancient times through the aftermath of World War II. For each historical period, the author examines the care the sick and wounded received in the field and in hospitals, the care given to the disabled veteran and his dependents, and who provided that care and how. He shows how the lessons of history have informed the American experience over time. Finally, the author sums up this history thematically, focusing on changes in the nature and treatment of injuries, organization of services on and off the battlefield, the role of the state in providing care, and the invisible wounds of war
Includes bibliographical references
Print version cataloged as a monographic set by Library of Congress
Keywords: Medical care; Diseases; Wounds and injuries; HISTORY / Military / Biological & Chemical Warfare; Medicine, Military; Medical personnel; HISTORY / Military / Veterans; Health